Entre ramos e rezas: o ritual de benzeção em São Luiz do Paraitinga, de 1950 a 2008 - Moura, Elen Cristina Dias de (2009)
The dissertation Between Ramos and Prayers: blessing practice in São Luiz do Paraitinga, from 1950 to 2008 is the result of a two year research performed in the city of São Luiz do Paraitinga on blessing ritual. Our goal was to study this popular form of cure to check the transmission resources, the ruptures and the continuities in the ritual along time and the relation established among faith healers and the local priests. By following the everyday routine of Catholic communities in cities of little and average size, we verify the men and women effective participation involved in religious practices of not official blessings. They are faith healers, people with a special power, able to control the forces able to cause physical, emotional and spiritual unbalances. By means of blessings, they guarantee the operation of the wished normality, breaking itself with the threatening unbalance of the existence. In spite of being to the process margin of the institutionalized religion, faith healers occupy highlight role and enjoy of certain authority in their communities. By talking about blessing ritual, we intend to contribute for the manifestations comprehension of the popular culture in a contemporary context. It is a research on the people and their manifestations, that is, of common people that bring in the everyday experiences an adaptation context to the lived reality. Concerning methodology, we employ magician's and priest concepts developed by Weber (1999), and of religious field, formulated by Bourdieu (2007), to explain the relation established among faith healers and the local priests. The information collection was made by means of the field research with some city inhabitants, besides priests and faith healers. To analyze the interviews content, we used the resources offered by the content analysis method